Evaluation of medicine retail outlets for sale of typhoid fever vaccine among adults in two urban and rural settings in western Kenya: a proof-of-concept study. Issue 1 (December 2016) - Ho, Julius; Odhiambo, Gladys; Meng'anyi, Lucy; Musuva, Rosemary; Mule, Joseph; Alaly, Zakayo; Odiere, Maurice; Mwinzi, Pauline; Ganley-Leal, Lisa
Abstract Background Private sector medicine outlets are an important provider of health services across the developing world, and are an untapped means of distributing and selling vaccines outside of childhood immunization programs. The present study assessed the viability of medicine outlets (chemists and pharmacies) as potential channels for sale of vaccines. Methods To evaluate the viability of the medicine outlet model, we partnered with nine outlets across urban and rural communities in western Kenya to sell a nurse-administered typhoid vaccine. Purchasers were surveyed to reveal market demographic characteristics, reasons for vaccine purchase, and sources of information about the program. Key informant interviews and focus group discussions defined acceptability, demand, and additional suggestions for improving this mechanism of selling and distributing vaccines. Results There was a higher than expected demand for the vaccine that resulted in stock-outs. Previous instance of typhoid, desire to prevent disease, affordable price and convenience were cited by most participants as main reasons for purchase of vaccine at the local outlet. The most common source of information on the vaccine sale was word-of-mouth and referral from friends. Longer vaccine sale duration, adequate stocking of vaccines and extended hours of administration in the evening to allow working individuals to buy vaccines were cited by participants as ways for improved participation in the future. Conclusions This study demonstrated a high demand for vaccines at community medicine outlets. Important insights on how to improve and sustain such a program included extension of distribution time, education of outlet keepers, and minimizing vaccine stockouts. With improved social marketing, infrastructure mapping, education and pricing schemes, medicine outlets could become a sustainable avenue for selling adult vaccines in emerging markets for both routine and pandemic vaccines.